Electrogastrography in Patients with Functional Dyspepsia, Joint Hypermobility, and Diabetic Gastroparesis - Abdullah Al Kafee,; Talar Cilacı,; Yusuf Kayar,; Aydın Akan, (Turkish Journal of Gastroenterology, 2022)
Background: Transcutaneous electrogastrography is a novel modality to assess the human stomach’s gastric myoelectrical activity. The purpose of this study was to compare functional dyspepsia, joint hypermobility, and diabetic gastroparesis patients with healthy control subjects in terms of gastric motility abnormalities through electrogastrography evaluations, and to then evaluate the correlation among variations in their blood parameters.Methods: This study analyzed 120 subjects with functional dyspepsia (n = 30), joint hypermobility (n = 30), diabetic gastroparesis (n = 30), and control subjects (n = 30). The electrogastrography parameters included the dominant frequency, dominant power, power ratio, and instability coefficient, which were analyzed preprandially and postprandially. Although there are similar studies in the literature, there is no other study in which all groups have been studied together, as in our study.Results: The electrogastrography results showed that preprandial dominant frequency (P = .031*), dominant power (P = .047*), and instability coefficient (P = .043*), and postprandial dominant frequency (P = .041*) and dominant power (P = .035*) results were statistically significant among the functional dyspepsia, joint hypermobility, diabetic gastroparesis, and control groups. There was no significant difference found in terms of power ratio (P = .114) values. However, only glucose (P = .04*) and calcium (P = .04*) levels showed statistical significance. Several blood tests including hemoglobin (P = .032*), creatinine (P= .045*), calcium (P = .037*), potassium (P= .041*), white blood cells (P = .038*), and alanine aminotransferase (P = .031*) also showed correlation with the dominant frequency, power ratio, and instability coefficient parameters.Conclusions: This joint methodology demonstrated that it is possible to differentiate between functional dyspepsia, joint hypermobility, and diabetic gastroparesis patients from healthy subjects by using electrogastrography. Moreover, the majority of patients showed adequate gastric motility in response to food.Cite this article as: Al Kafee A, Cilacı T, Kayar Y, Akan A. Electrogastrography in patients with functional dyspepsia, joint hypermobility, and diabetic gastroparesis. Turk J Gastroenterol. 2022;33(3):182-189